Low-power sensor interfaces for detection of sporadic events : doctoral thesis - Gazivoda, Marko (M. Gazivoda, Fakultet elektrotehnike i računarstva, 2022)
The focus of this thesis was on wake up sensor interfaces used for lowering sensor node power consumptions. The interfaces’ intended application was detection of sporadic transient events in the lower acoustic spectrum (up to 2.5 kHz), lasting up to a few seconds. The passing speedboat event was chosen as a representative event. Acoustic signal features were analyzed, and a set of criteria was developed to determine the feature’s applicability in low power interfaces for passing speedboat detection. Based on the criteria, the spectro temporal decomposition and level crossing rate interface architectures were explored further. Interface prototypes were developed and functionally tested. The results showed both architectures were applicable for passing speedboat detection, with true positive detection rates exceeding 90%. They also showed the level crossing rate architecture was operational with two times lower inputs, required 40% less area and components to implement and had over three times lower power consumption. As a solution for the spectro temporal decomposition architecture’s envelope detector chokepoint, two feature extractors were proposed and developed, one utilizing an electrically and the other a mechanically switched inductor. The feature extractors achieved 43% and 72% lower power consumptions and had four and two times lower minimal input voltage, respectively, compared to the conventional spectro temporal decomposition interface, demonstrating the advantages of the switched inductor in low power sensor interfaces for event detection.